Technology Review: Image Enhancement, Feature Extraction and Template Protection of a Fingerprint Authentication System - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (Asian Network for Scientific Information (ANSINET), 2010)
Nowadays, biometric technologies are turning into the basis of a widespread array of vastly secure recognition and authentication solution for an individual. Biometric recognition is the automated detection of a human being that is based on behavioral or physiological characteristics. The need for highly secure detection and personal verification technologies is becoming apparent, as the level of security breaches and transaction fraud increases. The core intention of this paper is to review the widespread research that has been done on the image enhancement, feature extraction as well as template protection of the fingerprint authentication system over the previous few decades. Especially, it discusses the techniques of enhancement, extraction and protection that have been implemented in order to solve the problem. To conclude, it illustrates experimental outcomes from the modern fingerprint authentication schemes that have been experienced with the FVC2004 Database.